Peningkatan Hasil dan Aktivitas Belajar Materi Teks Eksplanasi dengan Model Think-Talk-Write Berbantu Media Komik Strip - Sudiyati Sudiyati (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Writing skills are one of the language skills that need to be developed and improved as a means of written communication. Writing must be done effectively and efficiently considering that writing is a productive and expressive activity. Improving writing skills needs to be done with an appropriate and efficient approach. In this case, the teacher as a facilitator plays an important role in choosing learning methods that are appropriate for learning writing skills. This classroom action research aims to improve learning outcomes and student learning activities by using the think-talk-write model assisted by comic strip media in learning to write explanatory texts. In this study, the research subjects were students of class XI MIPA 2 SMA Negeri 6 Semarang for the 2022/2023 academic year. The indicator of the success of this research is the learning outcomes and activities of students in class in cycle 1 being able to achieve an average score for each aspect that is ≥ 75% or in good criteria and in cycle 2 it increases to ≥ 75%. The average score showed an increase from 73.03 in cycle I to 78.35 in cycle II. The average increase in learning outcomes is low due to several factors, namely students are focused on rewriting content in comics, do not insert a more varied vocabulary, and often make mistakes in spelling, punctuation, use of capital letters, and arrangement of paragraphs. Meanwhile, student learning activities increased from 58.33% in cycle I to 86.11% in cycle II. Based on the results of the classroom action research that has been done, it is concluded that learning explanatory text using the think-talk-write model assisted by comic strip media is able to improve learning outcomes and learning activities for class XI MIPA 1 students of SMA Negeri 6 Semarang in the academic year 2022/2023.